Role of Mitochondria-Associated Endoplasmic Reticulum Membrane in Inflammation-Mediated Metabolic Diseases - Themis Thoudam; Jae-Han Jeon; Chae-Myeong Ha; In-Kyu Lee (Mediators of Inflammation)
Inflammation is considered to be one of the most critical factors involved in the development of complex metabolic diseases such as type 2 diabetes, cancer, and cardiovascular disease. A few decades ago, the discovery of mitochondria-associated endoplasmic reticulum (ER) membrane (MAM) was followed by the identification of its roles in regulating cellular homeostatic processes, ranging from cellular bioenergetics to apoptosis. MAM provides an excellent platform for numerous signaling pathways; among them, inflammatory signaling pathways associated with MAM play a critical role in cellular defense during pathogenic infections and metabolic disorders. However, induction of MAM causes deleterious effects by amplifying mitochondrial reactive oxygen species generation through increased calcium transfer from the ER to mitochondria, thereby causing mitochondrial damage and release of mitochondrial components into the cytosol as damage-associated molecular patterns (DAMPs). These mitochondrial DAMPs rapidly activate MAM-resident inflammasome components and other inflammatory factors, which promote inflammasome complex formation and release of proinflammatory cytokines in pathological conditions. Long-term stimulation of the inflammasome instigates chronic inflammation, leading to the pathogenesis of metabolic diseases. In this review, we summarize the current understanding of MAM and its association with inflammation-mediated metabolic diseases.